2014
DOI: 10.4172/2155-9619.1000177
|View full text |Cite
|
Sign up to set email alerts
|

Boron Carbide Particle as a Boron Compound for Boron Neutron Capture Therapy

Abstract: Background: In boron neutron capture therapy (BNCT), the intravenous administration of boron-containing compounds such as boronophenylalanine (BPA) and borocaptate sodium (BSH) is followed by irradiation with thermal neutrons. In the present study, we determined whether a boron-rich boron carbide (B 4 C) nanoparticle could be used for BNCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…PLML can produce submicrometre spherical particles of various materials, such as metals [7,8], oxides [5,6,9], semiconductors [10,11] and carbides [3,4]. Given the unique features of submicrometre spherical particles—including their dispersibility, stability, crystallinity and sphericity—applications utilizing optical [5,12], medical [13], mechanical [14,15] and magnetic [16] functionality have been examined.…”
Section: Introductionmentioning
confidence: 99%
“…PLML can produce submicrometre spherical particles of various materials, such as metals [7,8], oxides [5,6,9], semiconductors [10,11] and carbides [3,4]. Given the unique features of submicrometre spherical particles—including their dispersibility, stability, crystallinity and sphericity—applications utilizing optical [5,12], medical [13], mechanical [14,15] and magnetic [16] functionality have been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Boron carbide (B 4 C), endowed with high neutron absorptivity, has been studied as a possible material for BNCT agents [ 156 ]. For example, Mortensen et al [ 94 ] evaluated the potential use of B 4 C NPs in T cell-guided BNCT, and, to improve cellular adhesion and uptake, functionalized their B 4 C NPs with the transactivator of transcription (TAT) peptide, proving their efficacy as BNCT agents in a murine melanoma model [ 95 ].…”
Section: Nanoparticles For Bnctmentioning
confidence: 99%
“…Recently, boron carbide was newly applied in medical applications, for example, as a carrier in boron neutron capture therapy (BNCT) [5]. This therapy uses the neutron capture reaction of the nuclei of non-radioactive boron, 10 B, which results in the unstable nucleus 11 B, which decays into an α particle and a recoiled lithium nucleus, 7 Li.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been reports on the use of boron carbide in BNCT therapy. One such research method consists of the treatment of oral squamous cell carcinoma with B 4 C particles encapsulated in a graphitic layer with an approximately 200 nm size, which resulted in the decrease in the survival of cells in vitro and the inhibition of tumor growth in vivo after exposure to a neutron beam [5,19]. Another in vitro study showed that murine EL4 thymoma cells and B16 F10 malignant melanoma cells loaded with coated boron carbide nanoparticles prior to exposure to neutron irradiation were able to inhibit the proliferative capacity of untreated neighboring cells [19].…”
Section: Introductionmentioning
confidence: 99%